2021
DOI: 10.1002/smll.202007334
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Bimetallic NiFe‐Based Hydroxides/Selenides Heterostructure Nanosheet Arrays for Highly‐Efficient Oxygen Evolution Reaction

Abstract: Developing cost‐effective and high‐efficiency electrocatalysts toward alkaline oxygen evolution reaction (OER) is crucial for water splitting. Amorphous bimetallic NiFe‐based (oxy)hydroxides have excellent OER activity under alkaline media, but their poorly electrical conductivity impedes the further improvement of their catalytic performance. Herein, a bimetallic NiFe‐based heterostructure electrocatalyst that is composed of amorphous NiFe(OH)x and crystalline pyrite (Ni, Fe)Se2 nanosheet arrays is designed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(79 citation statements)
references
References 70 publications
1
75
0
Order By: Relevance
“…Meanwhile, there has been a significant decline in the intensity, suggesting that there are obvious changes in the coordination conditions of the Ni atoms during the voltage increase from 1.34 to 1.45 V. According to the absorption edge of the Ni K‐edge XANES plots in Figure S22a in the Supporting Information, the edges for 1.34 and 1.37 V have almost no shift, while the conditions of 1.43 and 1.45 V show an obvious right‐shift, suggesting an increase of the valence state of Ni as the voltage rises from 1.37 to 1.43 V. Based on the polarization plot of Ir@IrNiO (Figure 4a), it is in the water absorbing stage at 1.34 V and changes into the Ni 3+ to Ni 4+ step at 1.37 V; after that, it will be O–O formation and O 2 evolution. Thus, the surface Ni 3+ sites first absorb OH groups to form Ni 3+ –OH and then Ni 4+ –O at 1.34 and 1.37 V, and at the conditions of 1.43 and 1.45 V, they change into Ni 4+ sites [ 48,51,52 ]…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, there has been a significant decline in the intensity, suggesting that there are obvious changes in the coordination conditions of the Ni atoms during the voltage increase from 1.34 to 1.45 V. According to the absorption edge of the Ni K‐edge XANES plots in Figure S22a in the Supporting Information, the edges for 1.34 and 1.37 V have almost no shift, while the conditions of 1.43 and 1.45 V show an obvious right‐shift, suggesting an increase of the valence state of Ni as the voltage rises from 1.37 to 1.43 V. Based on the polarization plot of Ir@IrNiO (Figure 4a), it is in the water absorbing stage at 1.34 V and changes into the Ni 3+ to Ni 4+ step at 1.37 V; after that, it will be O–O formation and O 2 evolution. Thus, the surface Ni 3+ sites first absorb OH groups to form Ni 3+ –OH and then Ni 4+ –O at 1.34 and 1.37 V, and at the conditions of 1.43 and 1.45 V, they change into Ni 4+ sites [ 48,51,52 ]…”
Section: Resultsmentioning
confidence: 99%
“…All these compounds are converted to NiFe-based oxides or hydroxides during the catalytic process, and these anions largely contribute to the catalytic reaction at the anode, so the research for more and more abundant anion tuning continues. [20,23,[28][29][30][31][32][33][34][35] The enhanced OER activity of NiFe-based sulfides is due to the increase in electrochemical surface area and defects during the reaction as well as the decrease in catalyst grain size. For NiFe-based oxides/(oxy)hydroxides, FeOOH as an active site is too strong for the adsorption of OH* intermediates generated during electrocatalytic reactions and may impair their OER properties.…”
Section: Anion Adjustmentmentioning
confidence: 99%
“…[75] The heterogeneous structure consisting of amorphous structure and crystalline phase structure could both increase the number of active sites and keep the structure of the catalyst stable during the reaction. [31,76,77] Zou et al reported a facile method to prepare the nanocomposite (Ni-Fe-OH@Ni 3 S 2 /NF) that consisted of amorphous Ni-Fe-OH and Ni 3 S 2 nanosheet arrays. Ni-Fe-OH@Ni 3 S 2 /NF showed remarkable OER activity at current densities of up to 1000 mA/cm 2 .…”
Section: Building Heterogeneous Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to their bulk counterparts, self‐supporting nanoarray electrodes are particularly suitable as large‐current‐density OER catalysts because of their abundant exposed active sites and enhanced surface permeability. Consequently, Ni/Fe‐based hydroxides have been the target of intense research focus [15–24] . In addition to increasing the surface activity and active sites, forming a strong coupling interaction between substrate and electrocatalyst (i. e., substrate effect) is a facile way to enhance the electrocatalytic performance of the self‐supported electrode [12] .…”
Section: Introductionmentioning
confidence: 99%